2010
DOI: 10.1038/ajg.2009.587
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fibrosis Worsening in Obese Patients With NASH Through Parenchymal Fibronectin, HOMA-IR, and Hypertension

Abstract: A semi-quantitative assessment of the amount of parenchymal Fn present at an early stage in obese patients with NASH is valuable for predicting the progression of fibrosis. Similarly, lobular Fn deposition may be a sensitive and early indicator of active fibrogenetic processes in the liver. Hypertension and higher HOMA-IR scores are other clinical independent risk factors that predict the progression of fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 24 publications
3
37
0
1
Order By: Relevance
“…Cell surface delivery of integrins, which are fibronectin-binding receptors, is also reduced in AnxA6 overexpressing cells, thereby impairing cell migration [12]. Fibronectin is a component of the extracellular matrix and a sensitive marker of liver fibrogenesis in NAFLD [13]. The proinflammatory cytokine TNF is involved in various aspects of NAFLD pathophysiology and its neutralization ameliorates murine NASH [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cell surface delivery of integrins, which are fibronectin-binding receptors, is also reduced in AnxA6 overexpressing cells, thereby impairing cell migration [12]. Fibronectin is a component of the extracellular matrix and a sensitive marker of liver fibrogenesis in NAFLD [13]. The proinflammatory cytokine TNF is involved in various aspects of NAFLD pathophysiology and its neutralization ameliorates murine NASH [14].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and insulin resistance are thought to play an important role in the pathogenesis of NAFLD (12,23,87,120,152). An elegant study identified ER stress as a molecular link between obesity and deterioration of insulin action in liver and adipose tissue (117).…”
mentioning
confidence: 99%
“…Although an association between hypertension and the development of HCC in NAFLD has not been directly demonstrated, an indirect association has been previously reported [25]. Hypertension is known to be one of the features of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…Hypertension is known to be one of the features of metabolic syndrome. Previous studies have shown that hypertension promotes liver fibrosis in patients with NAFLD [25], and that liver fibrosis is a predominant risk factor for the development of HCC [18].…”
Section: Discussionmentioning
confidence: 99%